Film Nation : Hollywood Looks at U.S. History, Revised Edition - Burgoyne, Robert, 1949- (Book collections on Project MUSE., 2010)
Events of the past decade have dramatically rewritten the American national narrative, bringing to light an alternate history of nation, marked since the country's origins by competing geopolitical interests, by mobility and migration, and by contending ethnic and racial groups. This book analyses films that give shape to the counternarrative that has emerged since 9/11 - one that challenges the traditional myths of the American nation-state.